Implementasi Inverse Kinematics Pada Lengan Robot Pengambil Sampah - Fitriani, Annisa Rizka (Fakultas Teknik dan Ilmu Kelautan, Universitas Hang Tuah, 2023)
Technological developments in the field of robotics are very rapid, various kinds of robots have been created to help human life. To support technological developments in Indonesia, many robots have been created. One of the robots being developed is a waste sorting robot. This waste sorting robot is a type of manipulator robot or robot whose mechanical system resembles the working system of a human hand and is able to place things precisely. Therefore, it is very important to pay attention to controlling the movement of the robot arm so that it can pick up the waste. In this research, the Inverse Kinematic method was used to control the movement of the robot arm so that it can pick up trash properly. From the research results, the application of Inverse Kinematic succeeded in making the robot arm move to pick up trash well. Meanwhile, the average coordinate error is obtained for all trash positions on the X-axis was 4,17%, the Y-axis was 6,83%, and the Z-axis was 5,64%.